Self-referentiality in narrative literary fiction: A strategy of autopoiesis or autodestruction? - Fort, Bohumil (Bohemica Olomucensia, 2021)
Narrative literary fiction, during its long-lasting development, has established and employed various self-referential techniques and strategies and even our non-expert, reader experience reveals that self-referentiality can take on multiple forms and cause various effects. Some of its forms are conventionally connected with a certain genre, period or trend, others are grounded in a writer's unique idiolect, some are just random. The study offers a general overview of the basic types of self-referentiality, a) structural (essential) self-referentiality, b) direct (iconic) self-referentiality, c) indirect (indexical) self-referentiality, and connects these types with particular narrative techniques in concrete fictional narratives. Moreover, the taxonomy of the ways in which self-referentiality both enforce and also weaken narrativity, a general quality of narratives influencing their consistency and coherence in the process of the reader's conceptualization of the narratives, is introduced in the second half of the study together with examples illustrating the findings. Self-referentiality in fictional narratives can thus function as an important means of narrative auto-poiesis as well as its auto-destruction.
Keywords: narrative; autopoiesis; self-referentiality; narrativity; fictional world